EFFORTS TO INCREASE IMPULSIVE PURCHASES THROUGH CONSUMER EMPOWERMENT ON TIKTOK SHOP LIVE STREAMING - Eggy Ramanda, Noveca; Aqmala, Diana (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
Impulsive buying behavior has become an increasingly common phenomenon in society. Impulsive buying is the tendency to make purchases without careful consideration, triggered by emotional impulses or instant desires. This behavior can have a significant impact, both for individual consumers and for the economy as a whole. Impulse consumption can provide temporary satisfaction and short-term pleasure, but in the long term it can lead to problems such as financial loss, unmanageable debt, and decreased psychological well-being. Therefore, this research aims to determine several factors such as social stimulus, perceived Innovativeness, perceived persuasiveness, and trust in influencing Impulsive Buying. The type of research used is quantitative research using the SEM PLS (Partial Least Square) analysis method. The data collection method in this research uses a questionnaire. A questionnaire is a way to collect data by providing respondents with a series of questions or written statements for them to fill in. The number of respondents in this study was 101, consisting of Tiktok users. Test results show that Perceived Persuasiveness has a positive influence on Trust and Trust also has a positive influence on Impulsive